2017
DOI: 10.7874/jao.2017.21.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Factors Prognostic of Season-Associated Sudden Sensorineural Hearing Loss: A Retrospective Observational Study

Abstract: Background and ObjectivesThis study examined whether the prognosis of sudden deafness was dependent on the time of onset and evaluated the factors affecting prognosis during each period.Subjects and MethodsPatients who developed sudden hearing loss from January 2005 to December 2015 were evaluated retrospectively. Meteorological data were obtained from the official website of the Korea Meteorological Administration. Factors prognostic of hearing recovery rate were analyzed.ResultsThe hearing recovery rate of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 16 publications
0
14
0
3
Order By: Relevance
“…The prognostic significance of 3D FLAIR images in SSNHL is an interesting matter . With regard to the prognosis of ISSNHL, one study concluded that the presence of an abnormality on labyrinthine MR imaging was a poor prognostic indicator, especially in those with severe or profound hearing loss .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognostic significance of 3D FLAIR images in SSNHL is an interesting matter . With regard to the prognosis of ISSNHL, one study concluded that the presence of an abnormality on labyrinthine MR imaging was a poor prognostic indicator, especially in those with severe or profound hearing loss .…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic significance of 3D FLAIR images in SSNHL is an interesting matter. 17,18 With regard to the prognosis of ISSNHL, one study concluded that the presence of an abnormality on labyrinthine MR imaging was a poor prognostic indicator, especially in those with severe or profound hearing loss. 16 Another study concluded that a high-intensity signal on 3D FLAIR MRI is a subsidiary phenomenon related to dizziness rather than a single poor prognostic factor, on the assumption that a hyperintensity in vestibular organs is related to the presence of vertigo.…”
Section: Clinical Applicability Of the Studymentioning
confidence: 99%
“…In the study conducted by Ryu et al [14] to evaluate whether prognosis of ISSNHL was associated with the initial season as well as the factors that may influence the prognosis in every season or not, they revealed that recovery rates of hearing of 318 patients did not show a significant difference by months and there was no correlation between mean temperature and daily temperature range in onset period of disease and recovery rates. This study revealed that recovery rates did not show a significant difference among patients with onset during these four seasons.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, general characteristics of the weather such as atmospheric pressure and temperature as well as their variation and covariation have been commonly investigated. [8][9][10][11][12][13][14] The results of studies assessing the relationship between ISSNHL and parameters of weather condition in the literature are different from the results of the studies we could reach. Our clinical observations revealed that the number of cases with ISSNHL increased in certain periods.…”
mentioning
confidence: 82%
“…For SSNHL, 45-65% of patients will regain their pre-loss hearing thresholds even without therapy, with average gains of 35 dB. Spontaneous recovery without treatment can occur within 2 weeks (30-80%), but the complete recovery occurs only in 35% of patients [Ryu et al, 2017].…”
mentioning
confidence: 99%